Performance evaluation and identification of drop call probability by using traffic parameter / Nadiah Kamaruzaman - Kamaruzaman, Nadiah (2014)
There are different performance determinant have been practiced in cellular network and drop call is one of the most important for those. With the rapid increase of users in Malaysia, it becomes very important that the Quality of Service (QoS) been highlighted by network operators with a view of improving it. The dropped call phenomenon is one of the most important elements of QoS in a large range well-known cellular network has been analyzed. From measured traffic parameter data,, we obtained the result. By using statistical evaluation of measured data taken from a real network, network operators are allowed to optimize system performance and also improving the quality of service.